Aquatic Insect (Larvae) Distribution and Assemblages at River Intakes in Pergau Lakes. Issue 1 (August 2020) - Syed Omar, Sharifah Aisyah; Rak, Aweng Eh; Hassan, Hasimah; Yusoff, Akrimah; Hajisamae, Sukree; Shukor, Aisah Md
Abstract: Aquatic insect larvae is one of the biotic component in aquatic ecosystem that helps in balancing aquatic ecosystems.Therefore, a survey conducted to determine the distribution and assembalges on aquatic insect larvae in Pergau Lake River Intakes. Samples were collected using Surber Net at seven river intakes in Pergau lakes namely Sungai Long (Intakes 1 and 2), Sungai Renyuk (Intakes 1, 2 and 3), Sungai Terang, and Sungai Suda. A total of 733 individuals were collected comprising seven orders (Ephemeroptera, Plecoptera, Trichoptera, Coleoptera, Diptera, Odonata and Lepidoptera) with 43 families and 70 genus. Sungai Renyuk recorded highest abundance of aquatic insects followed by Sungai Long with 602 individuals and 110 individuals respectively. The lowest abundance of aquatic insect was at Sungai Suda which only two insecta orders found namely Diptera(Chironomidae) and Coleoptera (Elmidae). Ephemeroptera (22%), Chironomidae (38%) and Elmidae (22%) were the common family found at all station excepts Sungai Suda intakes that only found Chironomidae and Elmidae. The resutls shows how aquatic insects larvae assamblage and distribute differently at seven intakes.